Occurrence of Gastrointestinal Adverse Events Upon GLP-1 Receptor Agonist Initiation With Concomitant Metformin Use: A Post Hoc Analysis of LEADER, STEP 2, SUSTAIN-6, and PIONEER 6 - Klein, Klara R.; Clemmensen, Kim K.B.; Fong, Edwin; Olsen, Søren; Abrahamsen, Trine; Lingvay, Ildiko (Diabetes care, 2024)
To assess the impact of concomitant metformin use on gastrointestinal adverse events during the initiation and titration of a glucagon-like peptide 1 receptor agonist (GLP-1RA). Using data from four clinical trials of liraglutide and semaglutide (Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results [LEADER], Semaglutide Treatment Effect in People with Obesity [STEP 2], Trial to Evaluate Cardiovascular and Other Long-Term Outcomes With Semaglutide in Subjects With Type 2 Diabetes [SUSTAIN-6], and Peptide Innovation for Early Diabetes Treatment [PIONEER] 6), we compared the incidence of gastrointestinal adverse events during GLP-1RA initiation and titration in participants with and without concomitant metformin use. Of 16,996 participants, 12,928 (76%) were treated with metformin. Concomitant metformin use did not increase the percentage of participants who developed gastrointestinal adverse events or their severity during the observation window. Among participants experiencing gastrointestinal adverse events, metformin use did not increase study product discontinuation. Within treatment arms (GLP-1RA and placebo), a numerically higher percentage of metformin nonusers experienced gastrointestinal adverse events and discontinued the study product compared with metformin users. Concomitant metformin use does not increase occurrence of gastrointestinal symptoms during GLP-1RA initiation or impact GLP-1RA discontinuation.